Trace-element and U-Pb data of metapelitic apatite during progressive greenschist- to amphibolite-facies Barrovian metamorphism - Central Alps - Isadora A Henrichs; David M Chew; Gary J O extquotesingleSullivan; Chris Mark; Cora McKenna; Paul Guyett (PANGAEA, 2019)
Supplement to: Trace-element (Mn-Sr-Y-Th-REE) and U-Pb isotope systematics of metapelitic apatite during progressive greenschist- to amphibolite-facies Barrovian metamorphism. Geochemistry, Geophysics, Geosystems, doi: https://doi.org/10.1029/2019GC008359. Sample description and locations are provided in Table 1. Whole-rock major and trace elements are presented in Table 2. Trace and U-Pb apatite data are provided in Table 3, and epidote SEM-EDS data are shown in Table 4.
Supplement to: Henrichs, IA et al. (2019): Trace-element (Mn-Sr-Y-Th-REE) and U-Pb isotope systematics of metapelitic apatite during progressive greenschist- to amphibolite-facies Barrovian metamorphism. Geochemistry, Geophysics, Geosystems, https://doi.org/10.1029/2019GC008359